Involvement of the cholinergic pathway in glucocorticoid-induced hyperinsulinemia in rats - Angelini, Nagela; Rafacho, Alex [UNESP]; Boschero, Antonio Carlos; Bosqueiro, José Roberto [UNESP] (Elsevier B.V., 2010)
Aims: We investigated the contribution of the cholinergic nervous system to dexamethasone-induced insulin resistance and hyperinsulinemia in rats.Methods: Seventy-day-old Wistar male rats were distributed in groups: control (CTL), vagotomized (VAG), and sham operated (SHAM). on the 90th day of life, half of the rats were treated daily with 1 mg/kg of dexamethasone for 5 days (CTL DEX, VAG DEX, and SHAM DEX).Results: In the presence of 8.3 mM glucose plus 100 mu M carbachol (Cch), isolated islets from CTL DEX secreted significantly more insulin than CTL. Cch-enhancement of secretion was further increased in islets from VAG CTL and VAG DEX than SHAM CTL and SHAM DEX, respectively. In CTL DEX islets, M3R and PLC beta 1 and phosphorylated PKC alpha, but not PKC alpha, protein content was significantly higher compared with each respective control. In islets from VAG DEX, the expression of M3R protein increased significantly compared to VAG CTL and SHAM DEX. Vagotomy per se did not affect insulin resistance, but attenuated fasted and fed insulinemia in VAG DEX, compared with SHAM DEX rats.Conclusion: These data indicate an important participation of the cholinergic nervous system through muscaric receptors in dexamethasone-induced hyperinsulinemia in rats. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Dexamethasone; Insulin resistance; Insulin secretion; Parasympathetic nervous system